Detecting seasonal and long-term vertical displacement in the North China Plain using GRACE and GPS - Wang, Linsong; Chen, Chao; Du, Jinsong; Wang, Tongqing (Hydrology and earth system sciences, 2017)
In total, 29 continuous Global Positioning System (GPS) time series data together with data from Gravity Recovery and Climate Experiment (GRACE) are analysed to determine the seasonal displacements of surface loadings in the North China Plain (NCP). Results show significant seasonal variations and a strong correlation between GPS and GRACE results in the vertical displacement component; the average correlation and weighted root-mean-squares (WRMS) reduction between GPS and GRACE are 75.6 and 28.9 % respectively, when atmospheric and non-tidal ocean effects were removed, but the annual peak-to-peak amplitude of GPS (1.2–6.3 mm) is greater than the data (1.0–2.2 mm) derived from GRACE. We also calculate the trend rate as well as the seasonal signal caused by the mass load change from GRACE data; the rate of GRACE-derived terrestrial water storage (TWS) loss (after multiplying by the scaling factor) in the NCP was 3.39 cm yr−1 (equivalent to 12.42 km3 yr−1) from 2003 to 2009. For a 10-year time span (2003 to 2012), the rate loss of TWS was 2.57 cm yr−1 (equivalent to 9.41 km3 yr−1), which is consistent with the groundwater storage (GWS) depletion rate (the rate losses of GWS were 2.49 and 2.72 cm yr−1 during 2003–2009 and 2003–2012 respectively) estimated from GRACE-derived results after removing simulated soil moisture (SM) data from the Global Land Data Assimilation System (GLDAS)/Noah model. We also found that GRACE-derived GWS changes are in disagreement with the groundwater level changes from observations of shallow aquifers from 2003 to 2009, especially between 2010 and 2013. Although the shallow groundwater can be recharged from the annual climate-driven rainfall, the important facts indicate that GWS depletion is more serious in deep aquifers. The GRACE-derived result shows an overall uplift in the whole region at the 0.37–0.95 mm yr−1 level from 2004 to 2009, but the rate of change direction is inconsistent in different GPS stations at the −0.40–0.51 mm yr−1 level from 2010 to 2013. Then we removed the vertical rates, which are induced by TWS from GPS-derived data, to obtain the corrected vertical velocities caused by tectonic movement and human activities. The results show that there are uplift areas and subsidence areas in NCP. Almost the whole central and eastern region of NCP suffers serious ground subsidence caused by the anthropogenic-induced groundwater exploitation in the deep confined aquifers. In addition, the slight ground uplifts in the western region of NCP are mainly controlled by tectonic movement (e.g. Moho uplifting or mantle upwelling).